Feed additives for swine: Fact sheets – flavors and mold inhibitors, mycotoxin binders, and antioxidants - Jacela, J.Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Renter, David G.; Dritz, Steven S. (My University, 2013)
Under the conditions of modern swine production, pigs need to be fed a balanced diet that meets their daily nutritional requirement for maintenance, growth, and reproduction. However, nutrient intake is largely determined by voluntary feed intake, which is greatly influenced by the chemical senses of olfaction and taste. Thus, it is essential to make sure that diets being offered to pigs are highly palatable to ensure high feed intake. This is especially important during times when pigs have decreased appetite, such as the first few days post weaning. Therefore, it is believed that enhancement of taste or smell through the use of flavors may help to improve the palatability of diets and, consequently, feed intake.
Keywords: Swine; Feed additives; Mold inhibitors; Mycotoxin binders; Antioxidants